Fog Image Restoration Using Dark Channel Prior Model with Gamma Transformation and Bilateral Filtering - Tyagi, Suman; Tiwari, Nirupma (International Journal of Computer Sciences and Engineering, 2025)
Images taken in foggy weather condition often suffer from poor visibility and clarity. Images of the outdoor scene which are captured under bad weather conditions contain atmospheric degradation such as haze, fog, smoke caused by the particles present in the atmosphere resulting in the absorption and scattering of the light, which travels from the scene point of the observer. In this paper, we define Dark Channel Prior Model, Gamma Transformation and Bilateral Filtering for fog removal and show better result.In this paper, to visibility increase with only single hazy image, a haze removal algorithm type is proposed. Firstly, the raw atmospheric transmission map is estimated with dark channel prior use.The experimental outcome shows that the good result as compared to previous gamma transformation and median filtering. The result based on the contrast gain ratio, execution time and entropy.